Formação e transformação químico-mineralógica da hematita em um geodomínio do Quadrilátero Ferrífero, Minas Gerais - Ana Rosa Passos Pereira (2010)
The present experimental work was devoted to the characterization of iron oxides and fluid inclusions in rock samples from the Fazendão mine, located in the east border of the Quadrilátero Ferrífero, Minas Gerais, Brazil, in an attempt to identify the main mineralogical pathway steps related to the transformation of magnetite (Fe3O4) to hematite (Fe2O3) in this iron ore deposit. Two specularite-rich samples and two samples with grains containing magnetite crystals were characterized with chemical analysis (X-ray fluorescence and dichromatometry for determination of total iron), chemically treated with dithionite-citrate-bicarbonate, magnetic measurements (saturation magnetization and magnetic susceptibility), powder X-ray diffraction (XRD) with a synchrotron light source, Rietveld structural refinement and Mössbauer spectroscopy; the fluids in rock inclusions, which are formed during the iron mineralization, were characterized by infrared microscopy and microthermometry. The samples were chemically identified as high-grade iron ore (>64 mass% Fe); hematite was identified as the major phase in all samples. From XRD data, magnetite, goethite and quartz were identified as minor phases. The presence of magnetite was also confirmed by measuring the saturation magnetization and magnetic susceptibility. From those data it was detected the characteristic Verwey transition (TV 115 K). From the Rietveld structural refinement it was determined the unit cell parameters for the each crystallographical phase. a-values so obtained for the rhombohedral hexagonal structureof hematite indicate some isomorphic replacement of Fe3+ by Al3+. However, this isomorphic substitution is effectively too small and the Morin transition (TM 260 K) could be still observed from the sign change of the electric field gradient, measured at the 57Fe nucleus with Mössbauer spectroscopy, by lowering the sample temperature from 298 K to 110 K. From chemical data for the fluids in rock-inclusions, two generations of specularite were identified: one, formed by an older, more saline, fluid and, other, a more recent, of a more dilute solution. Values of the eutectic point, measured with microthermometry, indicated that Ca2+, Mg2+ and Fe2+ are cations composing the fluids. These results are consistent with a mineralogical pathway model by which magnetite in this mine is oxidized and directly transformed to hematite, without intermediately forming maghemite (Fe2O3).